2005
DOI: 10.1577/t03-011.1
|View full text |Cite
|
Sign up to set email alerts
|

Status, Population Dynamics, and Future Prospects of the Endangered Kootenai River White Sturgeon Population with and without Hatchery Intervention

Abstract: Synthesis of sampling data from 1977 through 2001, including extensive mark-recapture data, provided a comprehensive and current picture of the status, population dynamics, and future prospects of the endangered Kootenai River white sturgeon Acipenser transmontanus. Natural recruitment was inconsistent in the 1960s, and with the additional impact of Libby Dam since the 1970s, the wild population now consists of an aging cohort of large, old fish. Jolly-Seber population estimates have declined from approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 36 publications
4
82
0
Order By: Relevance
“…The most rigorous analysis of recruitment failure to date reported that recruitment declined during the 1950s, but was further impacted by construction and operation of Libby Dam in 1972 (Paragamian et al 2005). …”
Section: B Sturgeon Spawning Incubation and Early Rearing Habitatmentioning
confidence: 99%
See 4 more Smart Citations
“…The most rigorous analysis of recruitment failure to date reported that recruitment declined during the 1950s, but was further impacted by construction and operation of Libby Dam in 1972 (Paragamian et al 2005). …”
Section: B Sturgeon Spawning Incubation and Early Rearing Habitatmentioning
confidence: 99%
“…Without immediate implementation of substantive habitat restoration measures, there will soon be too few wild adults to benefit from habitat improvements. Even with continued natural recruitment by remnant adults, future natural production must rely upon reproduction of hatchery produced Kootenai River fish after significant numbers reach sexual maturity (Paragamian et al 2005). …”
Section: B Sturgeon Spawning Incubation and Early Rearing Habitatmentioning
confidence: 99%
See 3 more Smart Citations